Analysis of Physics Concepts in Gasing Games - Dimas Fahmi Rizaldi; Fadlilatul Atiqoh; Dwikoranto Dwikoranto; Binar Kurnia Prahani; Firmanul Catur Wibowo; Sri Astutik (IKIP Widya Darma Surabaya, 2023)
The gasing game is a game where the gasing can rotate on an axis and balance at one point. This game is classified as one of the traditional games in Indonesia which is starting to disappear. One way to preserve this game is to integrate it with learning at school. Therefore, the authors are interested in studying the physics concepts contained in tops so that they can be used during physics learning activities in class. The method used in this study is a qualitative method, which is a procedure that produces descriptive data in the form of written or spoken words from people or observable behavior. Based on the research that has been done, it can be concluded that there are many physics concepts in top games, including the balance of rigid bodies, frictional forces, work, moments of inertia, and rotational motion, as well as kinetic energy as well as gravitational forces. So that traditional gasing games can be integrated with physics learning at school with the hope that students will learn physics more easily so that students have the desire to always study physics and be able to understand physics material properly and optimally.